On the physical parameters of the stellarator – source of neutrons with neoclassical losses, taking into account recycling and bohm losses - Rudakov, V.A. (Problems of Atomic Science and Technology, 2023)
The results of calculations of the physical parameters of the stellarator used as a neutron source for initiating nuclear reactions in a blanket of a hybrid reactor are presented. The calculations were carried out assuming the implementation of neoclassical transport processes, taking into account recycling and Bohm losses. The crushing effect of Bohm diffusion on the results of neutron yields is shown. Наведено результати розрахунків фізичних параметрів стеларатора, що використовується як джерело нейтронів для ініціювання ядерних реакцій в бланкеті гібридного реактора. Розрахунки проводилися у припущенні реалізації неокласичних транспортних процесів з урахуванням рециклінгу та бомівських втрат. Показано руйнівну дію бомівської дифузії на результати виходу нейтронів.